FAKTOR - FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BEI - Yunita - Putri (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to determine the effect of current ratios, cash flow, leverage, intangible assets and profitability on financial distress. The population and sample in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling method in this study using purposive sampling method and obtained 95 companies. The results showed that the Current Ratio had an effect on Financial Distress. The greater the Current Ratio, the lower the Financial Distress. Because when the Current Ratio has a high value, the company has the ability to meet its short-term obligations by using available current assets. The test results between the Cash Flow (CF) variable and the Financial Distress (FC) variable show that Cash Flow has an effect on Financial Distress. The higher the company's cash flow, the more likely the company will experience financial distress. For the test results between the leverage variable and the financial distress variable, it shows that the leverage variable has an effect on financial distress. The test results between the Intangible Asset variable and the Financial Distress variable show that the Intangible Asset variable has an effect on Financial Distress. If the Intangible Asset value increases, the Financial Distress value (Z-score) decreases. The results of testing the profitability variable with the Financial Distress variable show that the profitability variable has an effect on Financial Distress. Companies with high profitability will reduce the risk of financial distress.). Keywords: Financial Distress, Current Ratio, Cash Flow, Leverage, Intangible Asset, Profitability.